Imunitas Sosial Dalam Penanganan Corona Virus Disease (Covid-19) Di Kampung Ifale Distrik Sentani Kabupaten Jayapura Papua - Rohmani Rohmani; Kismiyati Kismiyati; Muhamad Sahiddin; Ardhanari H. Kusuma (ASMAT JURNAL PENGABMAS, 2021)
Abstract On March 21, 2020, the Papua Provincial Health Office announced the first case of Covid-19 in Papua Province. The number of cases that were reported positive were 2 people in Merauke Regency. The second latest case was reported simultaneously on March 22 in two regions, namely in Jayapura City 5 people and Mimika Regency 3 people. Data update on Covid-19 cases in Papua on May 2, 2020, cumulative positive cases were 240 cases, Patients under Supervision (PDP) were 240 cases and People under Monitoring (ODP) were 2,275 cases. The data update on May 2, 2020 also shows a cure rate of 59 cases (24.58%) and a death rate of 7 cases (2.9%). Clean and Healthy Life Behavior (PHBS). We plan to conduct health education about hand washing with soap (CPTS), how to use a mask correctly, how to remove a mask correctly, cough etiquette, disinfecting people's homes and churches, counseling about physical distancing (keeping a distance). The methods used in community service are health education, blood pressure measurement demonstrations, effective coughing, the use of masks, spraying disinfectants, and how to wash hands with soap. The results of community service are that the most people aged 51 years and over are 11 people (21.6%), The gender who participates in the activity is 27 men (52.9%), the education that participates in community service is high school amounted to 14 people (27.5%), the most occupations were housewives totaling 15 people (29.4%). Public knowledge about participants' covid-19 before and after counseling the average difference was 16.57 (80.29 – 63.72). The conclusion is that there is an increase in knowledge before and after community service is carried out in Ifale Village. Abstrak Pada tanggal 21 Maret 2020 Dinas Kesehatan Provinsi Papua mengumumkan kasus pertama Covid-19 di Provinsi Papua.Jumlah Kasus yang di laporkan positif ada 2 orang di Kabupaten Merauke. Kasus terbaru kedua dilaporkan serentak tanggal 22 Maret di dua Wilayah, yaitu di Kota Jayapura 5 orang dan Kabupaten Mimika 3 orang. Update data kasus Covid – 19 di Papua pada tanggal 2 Mei 2020, kasus kumulatif positif sebanyak 240 kasus, Pasien dalam Pengawasan (PDP) sebanyak 240 kasus dan Orang dalam Pemantauan (ODP) sebanyak 2.275 kasus. Update data 2 Mei 2020 juga menunjukkan angka kesembuhan sebanyak 59 kasus (24,58%) dan angka kematian sebanyak 7 kasus (2,9%). Perilaku Hidup Bersih dan Sehat (PHBS). Kami berencana akan melakukan penyuluhan kesehatan tentang cuci tangan pakai sabun (CPTS), cara menggunakan masker yang benar, cara melepaskan masker yang benar, etika batuk, melakukan disinfektan dirumah warga dan gereja, penyuluhan tentang physical distancing (jaga jarak).Metode yang dilakukan dalam pengabdian masyarakat yaitu dengan pendidikan kesehatan, demonstrasi pengukuran tekanandarah, batu ke fektif, penggunaan masker, penyemprotan disinfektan, dan cara cuci tangan pakai sabun. Hasil dari pengabdian masyarakat yaitu umur masyarakat paling banyak berusia rentang 51 tahun ke atas berjumlah 11 orang (21,6%), Jenis kelamin yang mengikuti kegiatan adalah laki-laki berjumlah 27 orang (52,9%), pendidikan yang mengikuti pengabdian masyarakat adalah SMA berjumlah 14 orang (27,5%), pekerjaan yang paling banyak adalah ibu rumah tangga berjumlah 15 orang (29,4%). Pengetahuan masyarakat tentangcovid -19 peserta sebelum dan sesudah penyuluhan selisih rata-rata adalah 16, 57 (80,29 – 63,72). Kesimpulan adanya peningkatan pengetahuan sebelum dan sesudah dilakukan pengabdian masyarakat di Kampung Ifale.